2015
DOI: 10.1519/jsc.0000000000000961
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Damage Response in Female Collegiate Athletes After Repeated Sprint Activity

Abstract: Glyn (2015) Muscle damage response in female collegiate athletes following repeated sprint activity. The Journal of Strength and Conditioning Research, 29 (10 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 40 publications
7
60
5
Order By: Relevance
“…Additionally, BTJ had no influence on any aspect of sprint performance, although perhaps our ability to detect any differences between groups was limited by the lack of change in performance between the two sprint tests. Nonetheless, the fact that sprint performance was unchanged seems to contrast with other studies who reported sprint times to still be slower than pre-exercise values up to 72 h after an RST similar to the present study [36,41,42]. Because the muscle-damaging RST was fairly similar between these studies (in fact, the one in the present study was designed to be more challenging), perhaps the divergent findings between these studies and the present one is due, in large part, to the different training status of the participants.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Additionally, BTJ had no influence on any aspect of sprint performance, although perhaps our ability to detect any differences between groups was limited by the lack of change in performance between the two sprint tests. Nonetheless, the fact that sprint performance was unchanged seems to contrast with other studies who reported sprint times to still be slower than pre-exercise values up to 72 h after an RST similar to the present study [36,41,42]. Because the muscle-damaging RST was fairly similar between these studies (in fact, the one in the present study was designed to be more challenging), perhaps the divergent findings between these studies and the present one is due, in large part, to the different training status of the participants.…”
Section: Discussioncontrasting
confidence: 90%
“…Indeed, previous literature appears to be equivocal on how well sprint and jump tests correlate. Some studies demonstrate that the time course of recovery for CMJ and sprint performance are not different after muscle-damaging RSE [36,41,42], while others agree with the present study [35,39,43], and have found that reductions in CMJ are more prolonged than sprint decrements. A recent study attempted to address this issue by comparing CMJ, drop jumps (DJ) and a 20 m sprint test after intermittent exercise and concluded that sprint performance seemed to recover more rapidly than both CMJ and DJ performance, both of which were still below pre-exercise values 72 h post-exercise [35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, comparisons between our results and those from Barak et al (2014) and Mendonca et al (2010) may not be appropriate. As we mentioned earlier, a plausible explanation for the difference between males and females in the high ASR group could be a higher anaerobic contribution during the RSA test in the high ASR males compared to the females, mostly due to their ability to develop more absolute speed and power during sprints (Keane, Salicki, Goodall, Thomas, & Howatson, 2015). Accordingly, the males of the high ASR group showed a significantly higher MSS compared to the rest of the groups, whereas the females of high ASR and low ASR groups exhibited similar values of MSS (Table 1).…”
Section: Discussionmentioning
confidence: 82%
“…While some have explored the RBE using sport-specific protocols (for instance intermittent sprint exercise (15), drop jump protocols (8) and downhill running (4)), other muscle damaging activities that can be directly applied to sport and exercise stimuli warrant further investigation. For instance, dance and multiple sprint sports such as soccer, rugby and basketball -popular activities that are participated in both recreationally and professionallyinvolve eccentric-biased activities (9,13,24,33). While these exercise modes differ in a number of respects (for instance dance is characterised by complex movement sequences often pre-choreographed, while the nature of repeated sprint sports means that movements are much more unpredictable), they both involve changes in velocity and direction; previously shown to elicit muscle damage.…”
Section: Repeated Bout Effect In Femalesmentioning
confidence: 99%